Effects of glutamine, glutamate, and aspartate on intestinal barrier integrity and amino acid pool of the small intestine in piglets with normal or low energy diet - Deng, Yuankun; Cheng, Hao; Li, Junyao; Han, Hui; Qi, Ming; Wang, Nan; Tan, Bi'e; Li, Jianjun; Wang, Jing (Frontiers in Veterinary Science, 2023)
, glutamate (glu) and glutamine (gln) are the major energy fuels for small intestine, and it had been indicated the mix of these three amino acid supplementations could maintain the intestinal energy homeostasis in our previous study. The aim of this study was to further investigate whether the treatment of gln, glu, and asp in low energy diet affects the intestinal barrier integrity and amino acids pool in weaning piglets. A total of 198 weaned piglets were assigned to 3 treatments: Control (Basal diet + 1.59% L-Ala); T1 (Basal diet + 1% L-Gln + 0.5% L-Glu + 0.1% L-Asp); T2 (Low energy diet + 1% L-Gln + 0.5% L-Glu + 0.1% L-Asp). Blood, jejunum and ileum were obtained on d 5 or d 21 post-weaning, respectively. Our results showed that T1 and T2 treatments increased the protein abundances of occludin, claudin-1, and claudin-3 in the small intestine, whereas decreasing the serum diamine oxidase (DAO) and D-lactate levels in weaning piglets. Meanwhile, T1 and T2 treatments significantly increased the small intestinal of positive rate of proliferating cell nuclear antigen (PCNA) promote intestinal cell proliferation. We also found that supplement with glu, gln, and asp improved the serum amino acid pool, and promoted ileal amino acid transporters gene expression of slc3a2, slc6a14, and slc7a11 in weaned piglets. Additionally, on the 21d post-weaning, T1 and T2 treatments stimulated the phosphorylation of mTOR-S6K1-4EBP1 signaling pathway in the small intestine, which may implicate the enhanced protein synthesis rate. In summary, dietary supplementation of gln, glu, and asp was beneficial to the intestinal barrier function, and amino acid pool regulation, while the benefits of gln, glu, and asp treatment might be diminished by the low energy diet. The results demonstrated that the supplementation of gln, glu, and asp under low energy level was preferentially supplied as the energy fuel to restore the gut barrier function in piglets on d 5 post-weaning. With the increase of age and intestinal maturation (on d